2015
DOI: 10.1051/0004-6361/201425577
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the KFR08 stellar stream

Abstract: The origin of the new kinematically identified metal-poor stellar stream, the KFR08 stream, has not been established to date. We present stellar parameters, stellar ages, and detailed elemental abundances for Na, Mg, Al, Si, Ca, Sc, Ti, Cr, Ni, Zn, Sr, Y, Zr, Ba, La, and Eu for 16 KFR08 stream members based on an analysis of high-resolution spectra. Based on the abundance ratios of 14 elements, we use the chemical tagging method to identify the stars with the same chemical composition that therefore might have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
5
1
Order By: Relevance
“…Thus, we question the debris origin for the streams, in which case their chemical compositions should be different from the thick disk stars. This is different from the Liu et al (2015) conclusion on a merger origin for the KFR08 stream. It is clearly seen that KFR08 has a wide metallicity distribution and its kinematics and chemistry are consistent with what is seen for the stars in the Galactic thick disk.…”
Section: The Origin Of the Arcturus Stream In This Studycontrasting
confidence: 93%
“…Thus, we question the debris origin for the streams, in which case their chemical compositions should be different from the thick disk stars. This is different from the Liu et al (2015) conclusion on a merger origin for the KFR08 stream. It is clearly seen that KFR08 has a wide metallicity distribution and its kinematics and chemistry are consistent with what is seen for the stars in the Galactic thick disk.…”
Section: The Origin Of the Arcturus Stream In This Studycontrasting
confidence: 93%
“…One major aim of the GALactic Archaeology with HERMES survey (GALAH; De Silva et al 2015) is to quantify this process and to trace individual stars back to the regions where they originally formed (Freeman & Bland-Hawthorn 2002;Bland-Hawthorn et al 2010). A main tool for this is the so-called chemical tagging, where elemental abundances are used to trace stars with a common origin (examples where chemical tagging has been applied, developed, and tested include De Silva et al 2007;Mitschang et al 2014;Blanco-Cuaresma et al 2015;Quillen et al 2015;Liu et al 2015;Ting et al 2016;Kos et al 2018;Andrews et al 2019;Simpson et al 2019). To this end, efficient and robust pipelines for the analysis of large numbers of single stars have been developed (Ness et al 2015;García Pérez et al 2016;Buder et al 2018;Ting et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the observed elemental abundances as well as the estimated ages are similar to those seen in the thick disk stars. Liu et al (2015) therefore conclude that the KFR08 stream is a kinematic stream that formed as a result of dynamical interactions among the Galactic disk stars.…”
Section: Chemistry Of Kinematically Interesting Starsmentioning
confidence: 78%
“…The nature of the stream, however, remains elusive due to the uncertainties in distances and kinematics as well as a small number of candidate member stars (Klement et al 2011). Liu et al (2015) analyzed high-resolution spectra for 16 candidate member stars of the KFR08 stream and estimated detailed elemental abundances of 14 elements. They have found that the 16 stars have a scatter in [Fe/H] as large as 0.29 dex and therefore, it is unlikely they originated from the same star cluster.…”
Section: Chemistry Of Kinematically Interesting Starsmentioning
confidence: 99%